Analyses of inter-firm governance and information technology. (20th April 2010) - Qi, Fei; Chen, Jim Q.; Chou, David C.; Guan, Qing Gary
This article discusses the impact of inter-organisational information systems over inter-firm governance. Based on the transaction cost theory, a theoretical model is proposed to describe the transformation of inter-firm governance in terms of market, hierarchical and bilateral modes. Four case studies are provided to support the theoretical conclusions. This study found that traditional inter-organisation information system (IOS) such as electronic data interchange (EDI) frequently erects new hierarchical inter-firm governance or enhances existing hierarchical governance. As IOSs moving towards internet-based and being affordable, their characteristics of market mode and bilateral mode are emerging. Especially, the recent emergence of web services technology is likely to expedite the trend. Web services technology provides an ideal platform for business to forge bilateral governance without transaction risks of traditional IOSs.